Prevalence of umbilical hernia of calves and its risk factors at Tangail Sadar of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study was done to investigate the prevalence of umbilical hernia of calves and its risk factors during the period from July, 2012 to January, 2013 at Tangail Sadar Upazila of Bangladesh. A total number of 1053 animals were examined during the study period where diagnosis based on the clinical history, clinical signs, palpation, needle puncture, auscultation. Then the animals was subdivided into some risk factors such as  age, sex, breed, history of umbilical infection which may be lead to umbilical hernia. It was observed that male (61.10%) were in more risk than that of female (38.90%). In case of male calves maximum occurrence of the disease were in the age group of 1-3 months (45.45%) followed by